2017
DOI: 10.1155/2017/8727164
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fishes and Invertebrates Living in the Vicinity of Energized and Unenergized Submarine Power Cables and Natural Sea Floor off Southern California, USA

Abstract: Increasing reliance on deep-water renewable energy has increased concerns about the effects of the electromagnetic fields (EMFs) generated by submarine power cables on aquatic organisms. Off southern California, we conducted surveys of marine organisms living around energized and unenergized submarine power cables and nearby sea floor during 2012-2014 at depths between 76 and 213 m. In general, EMFs declined to background levels about one meter from the cable. We found no statistical difference in species comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Hieronder wordt ingegaan op de bevindingen van acht publicaties die de potentiele effecten van EMF op vissen hebben onderzocht (Gill et al, 2012;Woodruff et al, 2013;Love et al, 2017aLove et al, , 2017bHutchison et al 2018;Wyman et al, 2018, Snoek et al, 2020 of gereviewd (Snoek et al, 2016(Snoek et al, , 2020.…”
Section: Elektromagnetische Straling / Barrièrewerking Door De Kabelunclassified
See 1 more Smart Citation
“…Hieronder wordt ingegaan op de bevindingen van acht publicaties die de potentiele effecten van EMF op vissen hebben onderzocht (Gill et al, 2012;Woodruff et al, 2013;Love et al, 2017aLove et al, , 2017bHutchison et al 2018;Wyman et al, 2018, Snoek et al, 2020 of gereviewd (Snoek et al, 2016(Snoek et al, , 2020.…”
Section: Elektromagnetische Straling / Barrièrewerking Door De Kabelunclassified
“…Daarnaast hebben Snoek et al (2020) een recente update gedaan van de internationale wetenschappelijke literatuur ten opzichte van hun eerdere review (Snoek et al, 2016), namelijk voor de periode 2017-2019, betreffende EMFs en effecten op marien leven in de Noordzee. -Zij beschrijven dat ook eerdere veldstudies (Love et al 2017a(Love et al , 2017b een gevarieerd beeld gaven:…”
Section: Elektromagnetische Straling / Barrièrewerking Door De Kabelunclassified
“…The BOEM has funded, and continues to fund, research projects to evaluate the effects on marine species from EMFs emitted by ocean power cables. Although electrosensitive species likely detect EMFs from power cables, the emissions are limited spatially to a few meters, reducing these species' potential exposure and the risk of impacts, especially when cables are shielded and buried [12][13][14][15]. Most research to date has concluded that there is likely little biological response to EMFs emitted by power cables [16,17], based on experimental approaches, mesocosms, large-scale field studies, behavioral studies, and measurements of EMFs from cables of various sizes [13,14,18,19].…”
Section: Partnerships and Collaborative Researchmentioning
confidence: 99%
“…Although electrosensitive species likely detect EMFs from power cables, the emissions are limited spatially to a few meters, reducing these species' potential exposure and the risk of impacts, especially when cables are shielded and buried [12][13][14][15]. Most research to date has concluded that there is likely little biological response to EMFs emitted by power cables [16,17], based on experimental approaches, mesocosms, large-scale field studies, behavioral studies, and measurements of EMFs from cables of various sizes [13,14,18,19]. Laboratory studies have been used to detect "dose-response" relationships, for example, how species behavior changes with exposure to EMFs [20].…”
Section: Partnerships and Collaborative Researchmentioning
confidence: 99%
See 1 more Smart Citation